2022
DOI: 10.1002/admi.202200480
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Antioxidant Structure in Mitigating Oxidation in Ti3C2Tx and Ti2CTx MXenes

Abstract: carbide MXenes (e.g., Ti 3 C 2 T x , Ti 2 CT x , V 2 CT x , Nb 2 CT x , etc.) are synthesized from their ceramic MAX phase precursor (with a formula of M n+1 AX n , where A is a group 13 or 14 element) by selectively etching the A phase using hydrofluoric acid (HF) or fluoride-containing aqueous solutions. [6][7][8][9][10] MXenes are known for their variety of surface terminal groups, excellent aqueous processability, and high electrical conductivity. [6][7][8][9][10] Extensive studies have focused on practica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 67 publications
2
23
0
Order By: Relevance
“…Here, converting MXenes into solid forms, such as powder or film [ 42 ], is one efficient way to extend their shelf-life; however, regaining their colloidal state necessitates an extra step of sonication, which poses a risk of rapid oxidation or flake shattering into smaller sizes. Among the reported strategies, MAX phase alteration [ 43 ], deaerated atmospheres [ 22 ], organic solvents [ 44 ], and antioxidants [ 45 ] have also proven effective in delaying the oxidation of MXenes. However, an effective method that could completely halt the spontaneous oxidation of MXenes in an aqueous environment is yet to be established.…”
Section: Strategies To Mitigate Mxenes Oxidationmentioning
confidence: 99%
See 3 more Smart Citations
“…Here, converting MXenes into solid forms, such as powder or film [ 42 ], is one efficient way to extend their shelf-life; however, regaining their colloidal state necessitates an extra step of sonication, which poses a risk of rapid oxidation or flake shattering into smaller sizes. Among the reported strategies, MAX phase alteration [ 43 ], deaerated atmospheres [ 22 ], organic solvents [ 44 ], and antioxidants [ 45 ] have also proven effective in delaying the oxidation of MXenes. However, an effective method that could completely halt the spontaneous oxidation of MXenes in an aqueous environment is yet to be established.…”
Section: Strategies To Mitigate Mxenes Oxidationmentioning
confidence: 99%
“… Copyright 2021, American Chemical Society. c Various antioxidant molecules and their antioxidation ability and corresponding digital photographs of Ti 3 C 2 T x dispersion during 14 days of storage, d the variation of Ti (IV) content of MXenes after 31 h of storage in aqueous media containing different antioxidants [ 45 ]. Copyright 2022, Wiley–VCH.…”
Section: Strategies To Mitigate Mxenes Oxidationmentioning
confidence: 99%
See 2 more Smart Citations
“…28 Several approaches have been proposed to mitigate the degradation of MXenes including addition of an antioxidant like sodium L-ascorbate, low temperature storage, and dispersion in polymers or in organic solvents. 26,[29][30][31] Our group has demonstrated that a higher 'n' composition helps in increasing the shelf lives of MXenes. 26 Additionally, our group has also showed that molten salt etched MXenes are less susceptible to degradation than acid-etched MXenes due to reduced content of oxygen-containing terminal groups.…”
Section: Introductionmentioning
confidence: 99%